Carbon farming in India: Case studies from Maharashtra and Telangana - Khurana, Ananya; Sainath, Banda; Adeeth Cariappa, Ajjikuttira Girish (CGIAR Initiative on Transforming Agrifood Systems in South Asia, 2023)
This research brief comprises two case studies about carbon farming projects which are currently running in the Indian states of Maharashtra and Telangana.